Psychometric Properties of the Healthy Lifestyle Beliefs Scale for Adolescents - Melnyk, Bernadette Mazurek (J Pediatr Health Care, 2021)
BACKGROUND: Healthy lifestyle behaviors are at the core of maintaining health. Understanding cognitive factors that influence these behaviors may be key in assisting individuals to adopt healthy lifestyle behaviors. OBJECTIVES: The aim of this study was to analyze the psychometric properties of the 16-item Healthy Lifestyle Beliefs Scale (HLB) that allows measurement of a person’s beliefs about their ability to live a healthy lifestyle. METHODS: Descriptive statistics were used to summarize sample characteristics and item characteristics of the 16 HLB scale items. Exploratory factor analysis (EFA) was conducted to identify the number of factors and factor structure underlying the HLB scale. Confirmatory factor analysis (CFA) was used to verify the factor structure derived from the EFA. Measurement invariance across gender and ethnic groups was examined by testing a sequence of nested multi-group CFA models by adding further constraints in each successive model to test three levels of measurement invariance. RESULTS: Cronbach’s alpha of the total scale was 0.894. The EFA scree plot identified two factors with eigenvalues greater than one. All factor loadings for factors 1 and 2 were greater than 0.40 and there were no items cross-loaded. A two-factor solution was retained for CFA. The final CFA model with correlated items had a better model fit, compared to the model with no correlated items. The measurement invariance results suggested that there was no gender difference in HLB measure in terms of factor structure, factor loading, threshold, and residual variances. DISCUSSION: The HLB scale was found to have adequate internal consistency and fit with the data. Findings show it is valid and acceptable for both boys and girls.